Research Agreement between Etiqa Family Takaful Bhd, Etiqa General Takaful Bhd and Universiti Teknologi MARA (UiTM) - Cawangan Kelantan, UiTM (2022)
This Research Agreement is entered into this 01 day of 10, of 2022 (hereinafter referred to as the "Agreement") between Etiqa Family Takaful Bhd (Co. No. 199301011506 (266243-D), a company incorporated in Malaysia under the Companies Act 2016 and having its registered business address at Level 19, Tower C, Dataran Maybank, No. 1, Jalan Maarof, 59000 Kuala Lumpur of (hereinafter referred to as "EFTB") the one part, Etiqa General Takaful Bhd (Company No. 201701025031 (1239197-A)), a company incorporated in Malaysia under the Companies Act 2016 with its registered address at Level 19, Dataran Maybank, No. 1, Jalan Maarof, 59000 Kuala Lumpur (hereinafter referred to as"EGTB") of the other part (Hereinafter both EFTB and EGTB collectively referred to as "ETIQA TAKAFUL") and Universiti Teknologi MARA, a public university established under Universiti Teknologi MARA Act 1976 (Act 173), whose address is Jalan limu 1/1, 40450 Shah Alam, Selangor (hereinafter referred to as "UiTM") of the other part.